2003
DOI: 10.1021/bp034129z
|View full text |Cite
|
Sign up to set email alerts
|

Size and Stability of Reconstituted Sesame Oil Bodies

Abstract: Oil bodies of sesame seeds comprise a triacylglycerol matrix, which is surrounded by a monolayer of phospholipids embedded with unique proteins, mainly structural proteins termed oleosins. Artificial oil bodies were successfully reconstituted with various compositions of triacylglycerols, phospholipids, and oil-body proteins. The sizes of reconstituted oil bodies displayed a normal distribution with an average size proportional to the ratio of triacylglycerols to oil-body proteins. Both thermostability and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 37 publications
5
72
0
Order By: Relevance
“…The sizes of artificial oil bodies could be controlled by changing the ratio of triacylglycerol over oil-body protein, whereas both thermostability and structural stability of artificial oil bodies decreased as their size increased, and vice versa [87]. For encapsulation of artificial oil bodies, recombinant oleosins expressed in Escherichia coli were found comparable to native oleosins isolated from seed oil bodies [141,142].…”
Section: Artificial Oil Bodies In Basic Research Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The sizes of artificial oil bodies could be controlled by changing the ratio of triacylglycerol over oil-body protein, whereas both thermostability and structural stability of artificial oil bodies decreased as their size increased, and vice versa [87]. For encapsulation of artificial oil bodies, recombinant oleosins expressed in Escherichia coli were found comparable to native oleosins isolated from seed oil bodies [141,142].…”
Section: Artificial Oil Bodies In Basic Research Studiesmentioning
confidence: 99%
“…It is demonstrated that the structural role of oleosin also protects Arabidopsis thaliana seeds against freeze/thaw-induced damage of their cells in vivo [82]. The contents of oleosins are found to determine sizes of seed oil bodies; presumably the ratio of oleosin over triacylglycerol is inversely proportional to the sizes of oil bodies [83][84][85][86][87][88]. The stability of isolated oil bodies could be substantially enhanced after their surface proteins were cross-linked by linker molecules, such as glutaraldehyde or genipin [87].…”
Section: Proposed Functions Of Oleosinmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with oil bodies, which are generally thought to be immobile in plant cells (27), peroxisomes are largely mobile and occasionally move across the cytoplasm in a microtubule-and actin filament-dependent manner in animals and plants, respectively (28 -30). Direct membrane associations between oil bodies and peroxisomes have been detected in mammalian cells, yeast, and plants (31)(32)(33).…”
mentioning
confidence: 99%
“…An alternative way to stabilize LDs may be to cross link the amphipathic arms of the oleosins; this has already been demonstrated in vitro by the chemical cross linking of artificial LDs with either gluteraldehyde or genipin (Peng et al, 2003). Recently, the sesame seed (Sesamum indicum) H-oleosin but not the L-oleosin was found to be ubiquitinated shortly after germination, and two of the three confirmed ubiquitination sites were located in the H-domain (Hsiao and Tzen, 2011).…”
mentioning
confidence: 99%